Meaning of People Names in Batak Karo Community, Juhar District, Karo Regency: Anthropolinguistic Study - Ethics, Novianti Bukit (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
Name is a word or group of words used to identify and mention the name of people, animals and places. This study aims to describe the meaning of people's names in the Karo Batak community in Juhar District, Karo Regency, which are the terms of giving names, types of people's names, categorization of meanings of people's names and cultural values ??in people's names in the Karo Batak community. This research uses the anthropoliguistic approach (cultural liguistic) put forward by Kridalaksana and Beratha which states that cultural linguistics is a study of the position and function of language in a broader social and cultural context which has a role in shaping and maintaining cultural practices and social structures of society. This study also uses the onomastic theory which states that semantics is the study of the relationship between linguistic signs and the things they sign. From the results of the data assessment, it can be concluded that the naming of people in the Batak Karo community in Juhar sub-district is done by means of custom in giving names. The types of names of people in the Karo Batak community in Juhar District are: pranama, kitik and merga. The names of people in the Batak Karo community in Juhar District contain the meaning of hope and the meaning of memories. Furthermore, the names of people in the Batak Karo community in Juhar District contain pragmatic values, namely formal connotations, non-formal connotations, male connotations and feminine connotations in line with Van Buren's opinion.